A Decade of Women’s Empowerment Research in Tourism: A Bibliometric Analysis (2014–2024) - Arisanti Ayu Wardhani; Ahmad Hafiyyan Shibghatalloh; Albertus Setyo Sumargo; Glenda Angeli (JOURNAL OF ADMINISTRATIVE AND SOCIAL SCIENCE, 2026)
This study aims to identify research trends related to women's empowerment in the tourism industry over the past ten years, from 2014 to 2024. The method used in this study is qualitative, using a literature review approach. The data was collected through the Scopus database, which resulted in 117 publication documents that met the criteria in the period 2014 to 2024. Data analysis was carried out using the VOSviewer application. The results of the study show that there are 117 publication documents related to women's empowerment in the tourism industry. However, the topic of women's empowerment has not been explored much from the perspective of tourism empowerment. Women's empowerment is considered important to be discussed in the context of tourism, as tourism activities provide new opportunities for women to access resources and employment. However, women's empowerment still faces various obstacles. Therefore, effective collaboration between stakeholders is needed to be able to increase women's empowerment, especially in the field of Tourism.